Four categories of patient participation in treatment and their linkage to decision-making in a structure of 81 models - Liv-Helen Heggland; Kjell Hausken (MDPI AG, 2015)
We clarify patient participation by developing a systematic structure of 34=81 models spanned out by three subcategories for each of four categories. Choosing a qualitative descriptive research design, and applying purposive sampling, four doctors, seven nurses, and seven patients were selected to ensure a broad representative sample with experts of varying ages and sexes from medicine and nursing. The preferences of these were mapped onto the theoretical structure. Applying content analysis, meaning units were identified, condensed and coded. The four categories information dissemination, formulation of options, integration of information and control were shown to be exhaustive, and mutually exclusive through time causing a topdown process where one occurs before the other through four stages. The three subcategories specify how patients, healthcare professionals, or both, operate within each category. That is, either patients are active in some sense that is specified, or healthcare professionals are active in some sense, or both are active. Delineating a structure of 34=81 models, based on four categories and three subcategories, gives a richer structure than what has earlier been available. This almost all-embracing structure enables pinpointing the exact nature of any culture involved in care of patients, which illuminates how the culture reflects or can potentially be altered to reflect values of patient care that we respect.